Implementasi Kitab Hidayatul Muta’allim dalam Upaya Membentuk Akhlak Siswa di MTs. Unggulan Al-Qodiri 1 Jember - rizal, syaiful; Kurniawan, Diki (Al-Riwayah : Jurnal Kependidikan, 2023)
Moral education is very important to form a generation that is intelligent, has good morals, is diligent, and is responsible. If not, there will be a decline in national values ​​and nobility. To prevent this, schools as a place of moral education are expected to be able to maintain nobility and national values ​​through various activities in them. The focus of the research studied in this study, namely how is the process, impact and advantages and disadvantages of the learning process of the Hidayatul Muta'allim book in an effort to shape student morals at MTs Unggulan Al-Qodiri 1 Jember? This study uses qualitative research and a phenomenological approach. The results of this study are 1) Implementation of the Hidayatul Muta'allim book forms the morals of students through the method of maximizing the power of the subconscious. 2) The results of the implementation of the Hidayatul Muta'allim book in the formation of student morals are included in 5 points: Student morals in relation to Allah and His Messenger, Student morals in relation to teachers, Student morals in relation to parents, Student morals in relation to others, the morals of students in relation to themselves. 3) The advantages of learning the Hidayatul Muta'allim book are the practical methods and the book which is easy to carry anywhere, while the drawback is the explanation which is less comprehensive.